Numerical Analysis of Air-Water Heat Exchanger as Passive Cooling System in Air Ventilation - Saputra, Firman Omni; Lapisa, Remon; Refdinal, Refdinal; Syahri, Budi (Asian Journal of Science, Technology, Engineering, and Art, 2023)
Indonesia has a humid tropical climate and many major cities are located along the coast, causing a large energy demand for thermal comfort. It takes a lot of energy to get thermal comfort. So one of the effective strategies for energy efficiency of HVAC (Heating, Ventilation, and Air Conditioning) systems is passive cooling techniques. Therefore, savings are made by using heat transfer devices as passive cooling in air vents. This research was conducted to see the comparison between experimental data and Computational Fluid Dynamic (CFD) simulations. The implementation method in this research was carried out on Solidoworks 2020 software. Based on experimental data, the inlet temperature is 32.35˚C, the outlet temperature is 28.4˚C and the water temperature is 27.58˚C and the mass flow rate is 0.0936 kg/s, the effectiveness is 0.228, then a variation with a mass flow rate of 0.1872 kg/s is obtained with an effectiveness of 0.122 and a mass flow rate variation of 0.2808 kg/s is obtained with an effectiveness of 0.083.